PEMBELAJARAN KRITIS-KREATIF DAN TRANSFORMATIF DI PONDOK PESANTREN - M. Taufik (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
Pesantren as a social-religious-institution has played a significant role in the dynamic of Indonesia nation. The role of the pesantren is not only concerned with educational and social-religious aspects but also broader, namely social transformation. In developing pluralism awareness in multicultural era, the pesantren has the important role. At the pesantren, there are many values that could be applied to meet the challenge. The existence of the pesantren, nowadays, is closely related to social affairs. Thus, to optimize this role, it is necessary to make a serious, systematic and sustainable effort because not all of the pesantren has the urge to do it.